The Role of Shopping Experience in Mediating the Relationship between Sensory Marketing and Customer Satisfaction: Evidence from Gajua Kopi V1 - Silmi Nabilah; Zulganef Zulganef (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study examines the role of sensory marketing in shaping customer satisfaction, with the shopping experience serving as a mediating mechanism in a coffee shop context. As competition in the café industry increasingly relies on experiential value, understanding how sensory stimuli translate into customer satisfaction becomes essential. Using a quantitative explanatory approach, data were collected from 160 visitors of Gajua Kopi V1 through structured questionnaires and analyzed using multiple regression and mediation analysis. The findings reveal that sensory marketing exerts a significant direct influence on customer satisfaction, indicating that sensory stimuli function as immediate value signals perceived by customers during consumption. In addition, sensory marketing significantly enhances the shopping experience, thereby positively affecting customer satisfaction. The mediation analysis confirms that shopping experience partially mediates the relationship between sensory marketing and customer satisfaction, suggesting that sensory stimuli influence satisfaction both directly and indirectly through experiential consolidation. These results highlight that customer satisfaction is not solely determined by functional product and service quality, but also by sensory marketing's ability to create a coherent, emotionally engaging shopping experience. Theoretically, this study contributes to experiential marketing literature by positioning shopping experience as a key explanatory mechanism rather than merely an outcome of sensory marketing strategies. Practically, the findings suggest that café managers should integrate sensory marketing elements with holistic experience design to optimize customer satisfaction. Future research is encouraged to extend this model by incorporating variables such as customer loyalty or brand image and applying it across broader service contexts